« Sortir du réel » et « entrer dans le surréel » chez Artaud - Martina Della Casa (Ksiegarnia Akademicka Publishing, 2017)
“Leave Reality” and “Enter Surreality”: Translation Encounters the Marvelous in Artaud’s Oeuvre Following the initial introductory section, which takes into account Artaud’s adaptations of Matthew G. Lewis and Lewis Carroll’s writings, as well as his comments on them, this project aims to examine the concept of the marvelous as conceived by the French writer and to demonstrate in what manner it constitutes a way of putting to a test the translation with respect to its writing in itself. In order to do so, after having laid the foundations of the issue in question, the objective of the second part of this article is to explore the marvelous in Artaud’s writings, discerning it from the concept of the marvelous in surrealism in order to contextualize it and better delineate its characteristics. The aim of the third section, instead, is to highlight the writer’s challenge towards representation, in all its forms, on the basis of the logic of the marvelous as it emerges from his texts. To conclude, the fourth part, following the path taken to this point, aims to reveal the relationship established by Artaud, between writing and the marvelous, but also between translatable and untranslatable.